Aberrant Hippocampal Network Connectivity Is Associated With Neurocognitive Dysfunction in Patients With Moderate and Severe Obstructive Sleep Apnea - Zhou, Li; Liu, Guiqian; Luo, Hong; Li, Huabing; Peng, Yating; Zong, Dandan; Ouyang, Ruoyun (Frontiers in Neurology, 2020)
Objectives: To explore the changes of functional connectivity(FC) within the hippocampus network in patients with moderate and severe obstructive sleep apnea(OSA) and its correlation with neurocognitive dysfunction to explore the potential neurophysiological mechanism． Methods: 32 treatment-naïve patients with moderate or severe OSA and 26 healthy controls (HCs) with matched age, gender, and education underwent the evaluations of Epworth sleep scale, neurocognitive function, full-night polysomnography, and resting-state functional magnetic resonance imaging scanning. The FC map of the hippocampus to other brain areas was compared among 15 OSA patients and 15 HCs with little head motion. Finally, the correlation between hippocampus FC strength and respiratory sleep parameters and neurocognitive assessments. Results: Compared with HCs, the right hippocampus showed significantly decreased FC with bilateral insular lobe, right thalamus, and right anterior cingulate gyrus (ACG), and increased FC with right superior and middle temporal gyrus, left posterior cingulate gyrus, and left angular gyrus in the patients with OSA．And the left hippocampus presented significantly decreased FC with left anterior cerebellum in patients with OSA. In addition, the aberrant right hippocampal FC with right ACG was significantly correlated with disease severity and disrupted sleep architecture in the OSA group. Furthermore, after adjusted related confounding factors, the FC strength between the right hippocampus and right insular lobe and right thalamus was positively associated with the scores of Stroop color-word test (SCWT) or Hopkins Verbal Learning Test-Revised (HVLT-R), while the FC between the right hippocampus and right middle temporal gyrus was negatively correlated with the scores of HVLT-R. The right hippocampus FC with right superior temporal gyrus, left angular gyrus, and ACG were all negatively related to the scores of symbol coding test (r=-0.642, p=0.045; r=-0.638, p=0.047; r=-0.753, p=0.012) respectively. The FC between the left hippocampal and left anterior cerebellar lobe showed a positive relationship with the scores of HVLT-R (r=0.757, p=0.011) and CPT-3D(r=-0.801, p=0.005). Conclusion: The hippocampus presented abnormal FC with cerebral and cerebellar regions extensively in OSA. Furthermore, the correlation between abnormal hippocampal network FC and neurocognitive dysfunction suggests a promising insight to explore the potential biomarker and pathophysiologic mechanism of neurocognitive dysfunction of OSA.